2019
DOI: 10.4025/actascibiolsci.v41i1.45262
|View full text |Cite
|
Sign up to set email alerts
|

Rapid green synthesis of silver nano particles from <i>Ziziphus mauritiana</i> and antibacterial activity against human pathogens

Abstract: A novel green source Ziziphus mauritiana fresh young leaves was opted to synthesize silver nanoparticles and analyze its antibacterial activity. The bioactive compounds present in the plant extracts reduced silver ions to NPs, indicated by change in color from red to dark brown. In this study, we have successfully synthesized nanoparticles using Z. mauritiana aqueous leaf extract as a reducing agent and the reaction process of synthesized nanoparticles was monitored by UV-Vis spectroscopy. The UV-Vis absorptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 22 publications
4
8
0
Order By: Relevance
“…Interpretations of Selvaraj et al (2019) are correlated with our findings . Similar results were also presented by Amutha and Sridhar …”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Interpretations of Selvaraj et al (2019) are correlated with our findings . Similar results were also presented by Amutha and Sridhar …”
Section: Resultssupporting
confidence: 93%
“…sativa are already reported. The availability of H + ions is considered responsible for the reduction of silver ions into silver NPs. Visual detection of the formation of green synthesized nanoparticles with the metal precursor and the plant extract is also confirmed by many researchers. , …”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…Various NPs of iron oxide have shown variable antibacterial activity against gram‐positive bacteria, including S. aureus and enterococcus, thereby confirming the results obtained in this study 69–71 . In the same light, many gram‐negative bacteria, including those reported in this study like P. aeruginosa and E. coli , have been shown to be susceptible to antibacterial effects of magnetic iron NPs 72–75 . The inhibition of fungal ( Candida ) species by magnetic iron oxide NPs reported in this study ascertains other findings that describe anticandidal activity that has been reported previously 76 .…”
Section: Resultssupporting
confidence: 90%
“…[69][70][71] In the same light, many gram-negative bacteria, including those reported in this study like P. aeruginosa and E. coli, have been shown to be susceptible to antibacterial effects of magnetic iron NPs. [72][73][74][75] The inhibition of fungal (Candida) species by magnetic iron oxide NPs reported in this study ascertains other findings that describe anticandidal activity that has been reported previously. 76 It has been noted that microbes have less resistance to NPs and usually show bacteriostatic and bactericidal susceptibilities toward nanomaterials.…”
Section: Antimicrobial Activitysupporting
confidence: 90%